Pedagogia do movimento como expressão da pedagogia socialista: a prática educativa do MST no II Enera - Silva, Janaine Zdebski da (2020)
It establishes relations between Pedagogy of the Movement and Socialist Pedagogy. It is part of the theme on the role of education in the struggle for social transformation with a view to socialist construction. It is constituted as documentary and bibliographic research. The objective is to apprehend expressions of Socialist Pedagogy in the educational practices of the MST, guided by the Movement's Pedagogy. It carries out an initial analytical approach with the ninety-five educational experiences of the MST socialized in the II ENERA. It shows convergences between the Movement Pedagogy matrices: social struggle; collective organization; job; history and culture; and the central dimensions of Socialist Pedagogy: radicalization of the public; omnilateral formation; job; actuality and struggles of the working class; knowledge; and self-organization and formation of collectives. For further analysis, it analyzes the ten educational practices of the MST-PR socialized in the II ENERA, having as reference the six central dimensions of Socialist Pedagogy. Synthesizes challenges, contradictions, advances and perspectives on the materiality of Socialist Pedagogy expressed in Movement Pedagogy. In the analysis of the educational practices of the MST - PR, by taking the dimension of radicalization of the public, it explains the contradiction of the double character of access to social rights under capitalism, which makes it possible to improve living conditions, but, contradictorily, contributes to maintaining of the social relations put in place. It points to the challenge related to the tension with the State to maintain and / or expand the autonomy of the social movement against state interference in pedagogical processes in a conservative way, given the natural class of the State. In the dimension of omnilateral formation, it shows actions that go beyond the limits of the bourgeois order, and that tension, not without limits and contradictions, unilateral formation, towards the integral formation of human beings. Regarding dimension of work, it indicates the challenge of deepening the understanding of the complex relationships between capital and labor and highlights the prospect of making the productive matrix of agroecology effective as a possibility in the construction of balanced relationships between human beings and nature. In the current dimension and struggles of the working class, it makes explicit the confrontation with capital and its materiality in the Brazilian field. It presents the construction of the Popular Agrarian Reform as a struggle that can generate an accumulation of forces towards social transformation. In the dimension of knowledge, it demonstrates that educational practices denounce the false neutrality of knowledge and conceive the understanding of the real from historical-dialectical materialism, linking knowledge to the challenge of transforming. Regarding the dimension of self-organization and formation of collectives, it highlights the contradictions and advances in the experience of “new values” amid the possibilities, limits and tensions in today's capitalist society. On the whole, it synthesizes the thesis that the educational practice of the MST based on the intention of a counter-hegemonic education, is anchored in, and at the same time produces, Socialist Pedagogy. In this statement, it reveals that Movement Pedagogy represents an exercise in the construction of Socialist Pedagogy of peasant origin in the context of the struggle for land in Brazil, which, in its historicity, reaffirms the link with historical-dialectical materialism and the centrality of work in counter-hegemonic educational construction and can become a reference pedagogy for the working class as a whole.